2019
DOI: 10.1002/nur.21948
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with women's desire for control of healthcare during childbirth: Psychometric analysis and construct validation

Abstract: The desire for control of healthcare is a significant moderator of outcomes related to childbirth. Researchers have shown that a sense of control of healthcare during childbirth is strongly correlated with postpartum maternal well‐being. The aims of this study were to examine (a) the psychometric characteristics of an instrument to assess women's desire for control of healthcare during childbirth, and (b) examine desire for control in relation to parity, medical complications of pregnancy, and women's choices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Additionally, the number of solutions suggested by EFA was evaluated with parallel analysis in Stata, similar to the work others have done in instrument development (Holm et al, 2018; Kahn, 2006; Stevens et al, 2019). Parallel analysis has been suggested as the gold standard for reducing dimensions in instrument development (Hayton et al, 2004; Patil et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the number of solutions suggested by EFA was evaluated with parallel analysis in Stata, similar to the work others have done in instrument development (Holm et al, 2018; Kahn, 2006; Stevens et al, 2019). Parallel analysis has been suggested as the gold standard for reducing dimensions in instrument development (Hayton et al, 2004; Patil et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring access to essential interventions in the LDRP is undisputed for those who have experienced pregnancy and childbirth complications. It has been reported that concerns about childbirth complications compel some women to opt for hospitals equipped with medical intervention and facilities [25]. Furthermore, compared to other women, those with a history of birth injuries have reported the need for supportive care and access to medical equipment.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, in hospital of many countries, a labor, delivery, recovery, and postpartum (LDRP) unit has been designed for family-centered care. Although women with high-risk pregnancies and complicated deliveries prefer to give birth in well-equipped hospitals [25], the evidence shows that despite the global efforts that have been made toward the development of physiologic delivery in maternity unit, the design of the delivery environment still needs reforms. Safe and satisfying delivery can be accurately planned by studying women's natural childbirth experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge derived from having a previous labor and birth was described as advantageous for achieving delayed admission, as was having a midwife or doula and self‐directed childbirth education or formalized attendance at community childbirth classes. Experiential knowing, gained from having a previous birth, promotes desire for decisional control during birth 31 . Women having their first birth demonstrated lower desire for control 31 and lower self‐efficacy 32 when compared with multiparous women.…”
Section: Discussionmentioning
confidence: 99%
“…Experiential knowing, gained from having a previous birth, promotes desire for decisional control during birth 31 . Women having their first birth demonstrated lower desire for control 31 and lower self‐efficacy 32 when compared with multiparous women. However, women having their first birth also describe feeling empowerment resulting from being able to stay home in early labor, which translated to making informed choices during the birth process 23 …”
Section: Discussionmentioning
confidence: 99%